Development of axion haloscopes for high-mass search at CAPP - Youn, SungWoo; Jeong, Junu; Semertzidis, Yannis K. (Frontiers in Physics, 2024)
The axion offers a well-motivated solution to two fundamental questions in modern physics: the strong CP problem and the dark matter mystery. Cavity haloscopes, exploiting resonant enhancement of photon signals, provide the most sensitive searches for axion dark matter in the microwave region. However, current experimental sensitivities are limited to the O(10 0 ) µeV range, while recent theoretical predictions for the axion mass favor up to O(10 2 ) µeV, suggesting the need of new experimental approaches that are suitable for higher mass regions. CAPP has developed/proposed several haloscopes effective for high-mass axion searches based on new cavity concepts and practical tuning mechanisms. They are characterized by large detection volumes and/or high quality factors at high frequencies, achieved by partitioning a single cavity into multiple cells, exploiting higher-order resonant modes, and constructing dielectric photonic crystal structures. Improving on the dish antenna haloscope scheme, a horn antenna array has also been proposed for volume-efficient broadband search in the THz region. We review these haloscope designs for sensitive search in the high-mass regions and discuss their impacts on future experiments.